Alpelisib-Induced Diabetes Mellitus: Case Report, Pharmacodynamics and Management Considerations - Pla Peris, Begoña; Arranz Martin, Alfonso; Ballesteros García, Anabel; Sebastián-Valles, Fernando; Marazuela Azpiroz, Monica (Frontiers in Endocrinology, 2022)
Introduction: Alpelisib is an orally selective PI3K alpha inhibitor recently available for the treatment of advanced breast cancer. PI3K pathway is an intracellular signaling pathway that plays an important role in regulating glucose metabolism. Hyperglycemia is the most common adverse event associated. Methods: We describe the case of a severe hyperglycemia associated with alpelisib treatment in a patient with metastatic breast cancer and previously near-normal glycemia. We analyse the clinical presentation, PI3K inhibitor pharmacodynamic aspects, its influence in glycemic control and the required treatment approach. Results: An important impairment of glycemic control was observed after initiation of alpelisib. In addition to insulin sensitizers drugs, intensive insulin regimen was necessary. Flash glucose monitoring (FGM) information has been helpful in understanding the pharmacodynamic aspects of alpelisib and insulin titration. Development of hyperglycemia is fast, already observed 24 hours after initiation of therapy. FGM shows severe and persistent hyperglycemia during most of the day, with a significant downward effect in the 4 hours after each daily intake, which evidences the strong but transitory effect of the drug enzyme blockade. C-peptide level is remarkable in accordance with drug pharmacodynamics, consistent with a significant insulin resistance. Conclusions: Glucose monitoring should always be performed in patients treated with alpelisib, especially in patients with diabetes and prediabetes. It is crucial to anticipate in these patients. Any delay can lead to a worsening in metabolic control resulting in the discontinuation or reduction of alpelisib, which would lead to a decrease in its effectiveness, and consecuently would deny patients an effective treatment with an impact on survival. Keywords PI3K inhibitor, alpelisib, hyperglycemia, diabetes mellitus, flash glucose monitoring (FGM)